Backtalk: The five intelligences of leadership. (May 2015) - Murphy, Joseph
Five intelligences comprise the DNA of leadership: banked intelligence, fluid intelligence, connected intelligence, relational intelligence, and operational intelligence. Thinking of the intelligences of leadership provides an especially robust architecture for analyzing the work, helping leaders understand why certain actions worked and why others did not and pinpointing where intelligences need to be enhanced.